Case report: Diagnosis of visceral leishmaniasis using metagenomic next-generation sequencing and bone marrow smear - Zhang, Xiaogang; Liu, Yanqing; Zhang, Mingming; Wang, Zhiqiang; Feng, Xing; Yang, Liu; Wang, Yajing; Liu, Juan; Zhao, Dongbao (Frontiers in Cellular and Infection Microbiology, 2022)
Visceral leishmaniasis (VL) is a chronic infectious disease transmitted by sandflies. The primary clinical manifestations are remittent fever, pancytopenia, and splenomegaly. As VL is rare with atypical symptoms, its diagnosis is often incorrect, missed, or delayed. Without appropriate treatment, the case fatality rate of symptomatic disease is more than 95%, but the prognosis is good if diagnosed and treated timeously. We report a case of VL that was diagnosed using metagenomic next-generation sequencing (mNGS) of a peripheral blood sample. By using mNGS and a bone marrow smear, we were able to make a timely diagnosis. The patient was treated with antimony, rapidly recovered, and was discharged from the hospital. This case illustrates the value of mNGS for making a timely diagnosis of VL.